Profile of Sinjai Superior Kampong Chicken (SSKC) Meat Colour Marinated with Pineapple Skin Powder - Azmi Mangalisu; Armita Permatasari (Serambi Journal of Agricultural Technology, 2019)
Kampong chicken is one of the local poultry that is generally raised by farmers in rural areas; the Kampong chicken farm business has great prospects, both economically and socially, because its products in the form of meat and eggs are highly nutritious food and high enough demand. The provision of pineapple skin was expected to be able to improve the quality of livestock products through enhancing the profile of SSKC meat colour that was contained in it, so it was necessary to do research on the effect of giving pineapple skin as a marinated meat ingredient for SSKC. Pineapple skin in this study was given in powder form to improve the profile of meat colour. The stages of this study carried out the process of marinating used pineapple peel powder with the specified marinating time. The samples were tested for colour profiles by measuring the brightness, redness and yellowish level of the flesh. The results showed that the colour profile was increasing with increasing levels of pineapple skin powder and marinating time. Based on these results, it can be concluded that the optimum profile of SSKC meat colour was at the level of 20% during soaking 120 minutes.